2018
DOI: 10.1590/0100-29452018547
|View full text |Cite
|
Sign up to set email alerts
|

Leaf nutrient content on seven plum cultivars with grafted by budding or own-rooted trees

Abstract: Several studies have been conducted in Brazil with rooting of plum scion cultivars, however, it is not known the performance and benefits of own-rooted trees at field. This study aimed to evaluate the leaf nutrient content (N, P, K, Ca, Mg, Fe, Mn, Zn, Cu and B) in seven Japanese plum cultivars (Prunus salicina) on the 2nd and 3rd year after field planting, whose nursery trees were produced by “T-inverted” budding method over ‘Capdeboscq’ peach (P. persica) or by own-rooted hardwood cuttings. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
1
0
3
Order By: Relevance
“…These results agree with those reported by [39], where there were no significant differences between grafted and non-grafted tomato plants. For K + contents, significantly higher values were also observed in grafted plants, similar to the work of Mayer et al [40], who found a higher K + content in grafted plums. The Mg 2+ content also increased in our grafted tomato plants, agreeing with similar results obtained by Milenković et al [41].…”
Section: Graft Effect On Mineral Contentsupporting
confidence: 89%
“…These results agree with those reported by [39], where there were no significant differences between grafted and non-grafted tomato plants. For K + contents, significantly higher values were also observed in grafted plants, similar to the work of Mayer et al [40], who found a higher K + content in grafted plums. The Mg 2+ content also increased in our grafted tomato plants, agreeing with similar results obtained by Milenković et al [41].…”
Section: Graft Effect On Mineral Contentsupporting
confidence: 89%
“…The rootstock has an effect on fruit quality (RADOVIC et al 2020, BENDER et al 2021), productivity, vigor, leaf nutrient contents (REIG et al 2018a, MAYER et al 2018, soil waterlogging tolerance (GUERRA et al 1992, RUBIO-CABETAS et al 2018, adaptation to heavy soils (REIG et al 2018b), and nematode resistance (PINOCHET et al 1999, PAULA et al 2011. Considering the importance of preserving the genetic identity of the rootstock, which is ensured by an efficient method of vegetative propagation, and that the rooting capacity varies according to the species and cultivar (STANICA 2007), it is essential to use a rootstock that is easy to propagate to enable the production of uniform nursery trees on a large scale (OLIVEIRA et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Uma das cultivares de ameixeira japonesa mais plantadas em nível nacional é a cultivar Letícia (EIDAM et al 2012, FIORAVANÇO et al 2015. As ameixeiras japonesas, juntamente com o pessegueiro e a nectarineira, são as frutíferas de caroço de importância comercial no Brasil (MAYER et al 2017, MAYER et al 2018.…”
Section: Introductionunclassified
“…As mudas de ameixeira, no Brasil, são tradicionalmente produzidas sobre porta-enxertos de pessegueiro, sendo o 'Okinawa' o porta-enxerto mais utilizado no Sudeste, e o 'A9', 'Capdeboscq' ou misturas de caroços de diversas cultivares tipo indústria, os mais utilizados na região Sul (FACHINELLO et al 2020, MAYER et al 2018. Porém, se o porta-enxerto não foi desenvolvido ou selecionado em função de vantagens agronômicas como sistema radicular, não há razão para a adoção de uma combinação interespecífica de enxertia (LORETI 2008, OLDONI et al 2019.…”
Section: Introductionunclassified
See 1 more Smart Citation